UJI AKTIVITAS ANTIINFLAMASI EKSTRAK METANOL, ETIL ASETAT DAN N-HEKSANA DAUN LAMUN (Enhalus Acoroides) PADA TIKUS GALUR WISTAR DENGAN INDUKSI KARAGENAN - Fatimah Munawaroh; Rani Prabandari; Galih Samodra; Adita Silvia Fitriana (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2023)
Inflammation is a response to damage to the tissue and infections that occur in the body's cells. Seagzador leaves Enhalus acoroides) contain secondary metabolites that are thought to have the potential as an anti -inflammatory agent. This study has the aim to understand the effect of the type of solvent on methanol extract, ethyl acetate and n-hexane seagrass leaf (Enhalus acoroides) on the foot edema of the wistar strain mice that is induced by carrageenan and know the value of AUC and %Dai. Anti -inflammatory testing is done by creating artificial edema in the foot of mice through 1%induction of carrageenan. The treatment is given to the test animals with the provisions: Group 1 is used as a negative control by administering 0.5%CMC Na, group 2 acts as a positive control that receives Na Diclofenac while groups 3, 4, and 5 are given methanol extract, ethyl acetate extracts, and N-hexane extract from Enhalus acoroides leaves dose 875 mg/kgBB. From the results of the study it is known that methanol solvents are more effective in inhibiting inflammation compared to extracts originating from ethyl acetate and n-hexane with an AUC value of 0.019 and %DAI of 39.834 %. Keywords: Anti-inflammatory, Enhalus acoroides leaves, %DAI